Two combinatorial patterns of telomere histone marks in plants with canonical and non-canonical telomere repeats - Adamusová, Kateřina; Khosravi, Solmaz; Fujimoto, Satoru; Houben, Andreas; Matsunaga, Sachihiro; Fajkus, Jiří; Fojtová, Miloslava (The Plant journal, 2020)
Telomeres, nucleoprotein structures at the ends of linear eukaryotic chromosomes, are crucial for the maintenance of genome integrity. In most plants, telomeres consist of conserved tandem repeat units comprising the TTTAGGG motif. Recently, non-canonical telomeres were described in several plants and plant taxons, including the carnivorous plant Genlisea hispidula (TTCAGG/TTTCAGG), the genus Cestrum (Solanaceae; TTTTTTAGGG), and plants from the Asparagales order with either a vertebrate-type telomere repeat TTAGGG or Allium genus-specific CTCGGTTATGGG repeat. We analyzed epigenetic modifications of telomeric histones in plants with canonical and non-canonical telomeres, and further in telomeric chromatin captured from leaves of Nicotiana benthamiana transiently transformed by telomere CRISPR-dCas9-eGFP, and of Arabidopsis thaliana stably transformed with TALE_telo C-3×GFP. Two combinatorial patterns of telomeric histone modifications were identified: (i) an Arabidopsis-like pattern (A. thaliana, G. hispidula, Genlisea nigrocaulis, Allium cepa, Narcissus pseudonarcissus, Petunia hybrida, Solanum tuberosum, Solanum lycopersicum) with telomeric histones decorated predominantly by H3K9me2; (ii) a tobacco-like pattern (Nicotiana tabacum, N. benthamiana, C. elegans) with a strong H3K27me3 signal. Our data suggest that epigenetic modifications of plant telomere-associated histones are related neither to the sequence of the telomere motif nor to the lengths of the telomeres. Nor the phylogenetic position of the species plays the role; representatives of the Solanaceae family are included in both groups. As both patterns of histone marks are compatible with fully functional telomeres in respective plants, we conclude that the described specific differences in histone marks are not critical for telomere functions.
Keywords: Plants; Nicotiana; epigenomika; Phylogeny; histone modification; telomery; Epigenomics; Arabidopsis thaliana; histonový kód; chromatin; Chromatin; epigenetics; Arabidopsis; Telomere; Histone Code; fylogeneze; tabák; telomeres; rostliny